VISUAL AND VERBAL IN LINE MESSENGER APPLICATION: A SEMIOTIC STUDY - Venice Wijaya; Tengku Thyrhaya Zein (JOALL (Journal of Applied Linguistics and Literature), 2020)
Nowadays, the usage of stickers especially in LINE Messenger is very popular, especially among teenagers. In spite of that, misunderstanding is still happen often. The reasons for choosing LINE stickers are that they are full-sized and expressive so many users can face a misunderstanding while using it. Also LINE provides a wide range of kind of stickers, and that it is very important for users to understand the meaning of each sticker to avoid misunderstanding. This study aims to identify the elements of visual and verbal signs contained in LINE messenger. The method used in this study is a qualitative descriptive method. The data used in this study is 20 visual (stickers) and verbal (texts), in which sticker is the main data meanwhile text is used as supporting data. The source of the data in this study is LINE Messenger. The data was then analyzed by using semiotic theory with a trichotomy model proposed by Charles Sanders Peirce. The results of the analysis show that every sticker contains qualisign aspects such as colors, gestures, etc., but not every meaning contain in the sticker is affected by their quality. It is also shown that every sticker is replica, but it still refers to the law. Every sticker must also share at least one similar characteristic or icon with the object they represents and the sticker used must base on the topic which occurred. The symbol is in the form of key word which makes it easier for the user to choose the sticker variations. Rheme and dicent show that meaning can be derived from the elements contain in the stickers. The differences are rheme contain qualisign and icon, meanwhile dicent only contain secondness aspects. Argument shows that meaning can be derived from hypotheses, standards in society, or even the sign itself. Keywords: LINE messenger, Sign, Visual, Sticker